PEMANFAATAN BGA (BUTON GRANULAR ASPHALT) SEBAGAI BAHAN PENGGANTI AGREGAT HALUS PADA CAMPURAN HRS-WC SECARA LABORATORIUM - Prawira, Abdi; Suparma, Latif Budi (Civil Engineering Forum Teknik Sipil, 2008)
Along with the improvement and development for keeping the road infrastructure in Indonesia, it is important to be far more comprehends and does testing to exploite nature material. The development of the existing firm layer material technology is very fast, to create technological innovation to efecienti cost, optimalisation of material exploition, expansion of natural material, and environmental friendliness like BGA (Buton Granular Asphalt) in the place of smooth aggregate at mixture HRS-WC. Exploition of BGA for the subsitution of fine aggregates done at this research through volume equivalent, using various comparison of fine aggregates used by BGA are (0%:100%), (25%:75%), (50%:50%) and (100%:0%). Method applied is Marshall and immersion, and determines optimum asphalt content from each various specimen. Specimen at optimum asphalt content was immersed Â½ hour (Marshall Standard) and 24 hours, then Marshall test is done. Marshall test and immersion are done to study the influence of various usage of BGA based on its stability values and indexs of retained strength. The result of this research shows optimum asphalt grade of specimen with various BGA of 0%, 25%, 50%, 75% and 100% is 6.37%; 4.85%; 4.49%; 4.15% and 4.55%. At Marshall standard various BGA 0%, 25%, 50%, 75% and 100% stability value of 1340 kgs, 1700 kgs, 1765 kgs, 1589 kgs and 1520 kgs is obtained while index of retained strength is 99.57%; 75.63%; 70.02%; 94.12% and 72.87%. These results show that utilization of BGA can reduce optimum asphalt grade, increase stability values and durability indexes on the HRS-WC mixture. Keywords : HRS-WC, BGA (Buton Granular Asphalt), Marshall.